The Impact of Rupiah Exchange Rate, Soybean Demand, and Production on Soybean Price Formation in Medan: An Islamic Economic Perspective - Agna Sabrina; Nurul Jannah; Muhammad Syahbudi (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This study aims to analyze the impact of the rupiah exchange rate (X1), soybean demand in Indonesia (X2), and soybean production in Indonesia (X3) on soybean price formation in Medan (Y), as well as to identify the relationships between these variables from an Islamic economic perspective. This research employs a quantitative approach, with analysis conducted using multiple linear regression and the ordinary least squares (OLS) model. Quarterly data from 2016 to 2023 was analyzed using E-Views software. The results indicate that the variables of the rupiah exchange rate, soybean demand in Indonesia, and soybean production in Indonesia have a significant simultaneous effect, with an F-Statistic value of 37.94889 and a probability (F-Statistic) of 0.0000 (